2017
DOI: 10.1111/codi.13869
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of sacral neuromodulation for chronic refractory constipation in children and adolescents: a Markov model analysis

Abstract: Chronic constipation seriously affects the quality of life of children and adolescents. Preliminary evidence suggests that SNM can improve symptoms and quality of life at a reasonable cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…This should be interpreted with caution as it was assumed that the effect of SNM remained unchanged. An excluded full‐text record assessed the cost‐effectiveness of SNM in children and adolescents with mixed FC subtypes and concluded that, from a healthcare perspective with a time horizon of 3 years, SNM might be a cost‐effective treatment option when compared with conservative treatment [45]. A mean ICER of €12 328 per QALY was reported in the base case analysis and ICERs ranged from €6422 per QALY to €36 652 per QALY based on sensitivity analyses [45].…”
Section: Discussionmentioning
confidence: 99%
“…This should be interpreted with caution as it was assumed that the effect of SNM remained unchanged. An excluded full‐text record assessed the cost‐effectiveness of SNM in children and adolescents with mixed FC subtypes and concluded that, from a healthcare perspective with a time horizon of 3 years, SNM might be a cost‐effective treatment option when compared with conservative treatment [45]. A mean ICER of €12 328 per QALY was reported in the base case analysis and ICERs ranged from €6422 per QALY to €36 652 per QALY based on sensitivity analyses [45].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, financial costs associated with SNS treatment can be substantial. 31 We therefore stress that patients and their families should be educated about the possible risks of both treatments in order to make an informed decision.…”
Section: Discussionmentioning
confidence: 99%
“…As was the case in all of these studies, for example, our model falls well short of representing clinical experience by failing to permit the possibility of recovering from a complication (in contrast, see van der Wilt et al (22) for an example of a cost modeling study in sacral neuromodulation that takes such recovery into account and the cost-utility analysis of sacral anterior root stimulation by Morlière et al ( 23) that integrates "reversible conditions," such as device failure, into its "irreversible states.") Annemans et al (9) describe the utility scores we adopted for this study, which were first published in 2009 (10) and which they (9) and Taylor et al (8) used in their studies, as "conservative" because in 2009 SCS equipment did not permit high-frequency stimulation, which Annemans et al believe has improved the effectiveness of SCS in treating low back pain.…”
Section: Strengths and Limitations Of Our Model And Its Inputsmentioning
confidence: 99%